Wind energy potential assessment for electricity and hydrogen production in Morocco’s southern regions - Younes El khchine (Energy Nexus)
Considering the high wind energy potential of some Morocco’s regions, this study evaluates the wind energy potential for electricity generation and hydrogen production in the Boujdour region, site Lamsid. Also, a techno-economic study was conducted to evaluate the viability and feasibility of hydrogen production based on wind energy. Wind energy potential is evaluated at different hub height using Weibull distribution function and various numerical methods based on the wind speed data collected over a 10-years period. Key indicators analyzed include: wind power density, electricity and hydrogen production and their respective costs, capacity factor of wind turbines and payback period of the system. This assessment was carried out employing thirty-seven commercially accessible wind turbines with rated power ranging from 330 kW to 3400 kW. Concerning wind speed distribution, some results revealed that the wind speed varies from 6.2 m/s, 7.2 m/s and 7.5 m/s recorded in October to 9.35 m/s, 10.2 m/s and 10.7 m/s in July at hub height of 50 m, 80 m and 100 m respectively. Moreover, the results indicated that the average monthly power density is approximately 588.8, 479.912 and 313.708 W/m2 at hub heights 100, 80 and 50 m respectively. These values are generally considered as good to excellent for wind-based electricity generation. The wind turbines EWT DW52 500, Repower MM100 50 Hz, and GoldWind GW140/3.0 exhibit the highest capacity factors, achieving 43.9 %, 41.44 %, and 49.36 % at hub heights of 50 m, 80 m, and 100 m, respectively indicating strong performance across varying elevations. Using these wind turbines, the electricity generation costs are 0.0529 $/kWh, 0.0561 $/kWh and 0.0471 $/kWh. Moreover, the annual volume of compressed hydrogen stored in the region is 845.685 m³, 3193.183 m³, and 5705.194 m³ at hub heights of 50 m, 80 m, and 100 m, respectively. Correspondingly, the hydrogen production costs at these hub heights were found to be 57.725 $/kg, 15.288 $/kg, and 8.556 $/kg, showing a notable reduction in cost with increasing hub height. In other hand, the use of wind turbines to generate electricity leads to avoid 11934.1, 83.0 and 38.9 ton/year of CO2, SO2 and NOx greenhouse gas emissions respectively using GoldWind GW140/3.0 wind turbine and to eliminate the annual emission treatment cost of 319432.1 $/year.